Useful outcome measures in INPH patients evaluation - Mori, Laura; Collino, Federica; Marzi, Annalisa; Pellegrino, Lucia; Ponzano, Marta; Chiaro, Davide Del; Maestrini, Sara; Caneva, Stefano; Pardini, Matteo; Fiaschi, Pietro; Zona, Gianluigi; Trompetto, Carlo; et al. (Frontiers in Neurology, 2023)
Idiopathic normal pressure hydrocephalus (INPH) is a neurological disorder, potentially reversible, clinically characterized by a specific triad of symptoms including gait disturbance, cognitive disorders and urinary incontinence. In INPH assessment, the most used test is the Timed Up and Go test (TUG), but a more comprehensive assessment would be necessary. The first aim of the present study is to verify the sensitivity of a protocol with both clinical and instrumental outcome measures for gait and balance in discriminating INPH patients. The second aim is to verify the most important spatiotemporal parameters in INPH assessment and their possible correlations with clinical outcome measures. Between January 2019 and June 2022 we evaluated 70 INPH subjects. We assessed balance performances with Berg Balance scale (BBS), Short Physical Performance Battery (SPPB) and TUGboth single (ST) and dual task (DT). We also performed an instrumental gait assessment with the GAITRite electronic walkway system, asking the patients to walk on the carpet for one minute at normal speed, fast speed and while performing a dual task. We compared the results with 20 agematched healthy subjects (HS). INPH patients obtained statistically significant lower scores at the BBS, SPPB and TUG DT, but not at the TUG ST, likely because the DT involve cognitive factors, altered in these subjects. Concerning instrumental gait evaluation, we found significant differences between HS and INPH patients in almost all spatio-temporal parameters except Cadence, which is considered a relevant factor in INPH guidelines. We also found significant correlations between balance outcome measures and gait parameters. Our results confirm the usefulness of BBS and suggest improving the assessment with SPPB. Although the TUG ST is the most used test in literature to evaluate INPH performances, it does not discriminate INPH; the TUG DT, instead, might be more useful. The GAITRite system is recognized as a quick and reliable tool to assess walking abilities and spatio-3 temporal parameters also in INPH patients and the most useful parameters are stride length, stride width, speed and the percentage of double support. Both clinical and instrumental evaluation may be useful in recognizing subjects at risk for falls.